Nano Phosphat Fertilizer of Chicken Bone Ash Effectivity by Foliar Application on Growth and Yield of Soybean (Glycine max L.) - Genesiska Genesiska; Mulyono Mulyono; Hanifah Amini (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2022)
Indonesian soybean production could not reach national needs. Thus to increasing of soybean productivity could be developed by using agricultural intensification through implementing nano technology on fertilizers that applied to new varieties of soybean. The aim of this research was to study the effect and determine the appropriate concentration of nano phosphate fertilizer from chicken bone ash via foliar application on growth and yield on soybean (Glycine max L.) variety Dega 1. This research was conducted with experimental method in polybag with a single factor treatment arranged in a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications: 100 % SP-36 fertilizer , 50% SP-36 fertilizer SP-36 + 0,1% nano phosphate, 50% SP-36 fertilizer +0,2% nano phosphate, dan 50% SP-36 fertilizer +0,3 % nano phosphate. Data research consists of growth and yield responses parameters and were analyzed by using ANOVA (Analysis of Variance) then continue analyzed with Duncan Multiple Range Test (DMRT) at α level 5%. The results revealed that various concentrations of nano phosphate fertilizer from chicken bone ash were effective to increase soybean growth and yield. Treatment of 50% SP-36 + 0,1% of nano phosphate choosen as best concentration.